BUDAYA MENYAMA BRAYA DALAM MENINGKATKAN KINERJA UMKM KELUARGA WARGA BALI DI KOTA MATARAM - I PUTU AGUS SANTANA; IDA BAGUS EKA ARTIKA (GANEC SWARA, 2024)
This research aims to explore the influence of the menyabraya culture on the performance of Balinese MSMEs in Mataram City, Lombok. Using quantitative methods, this research involved 100 respondents selected from a population of 1,365 business actors, based on the Slovin formula. There is a research gap that indicates a lack of empirical studies on the contribution of local culture to economic performance, especially in the context of migration. The novelty of this research lies in the emphasis on a culture of equality as a key variable that can strengthen social networks and collaboration among MSME players. The results of analysis using Structural Equation Modeling (SEM) software based on Partial Least Square (PLS) show that a culture of equality has a positive and significant influence on the performance of MSMEs. This conclusion indicates that the values of solidarity and cooperation in this culture are able to encourage increased productivity and innovation among business actors. The contribution of this research provides valuable insight for MSME actors and policy makers in designing empowerment strategies based on local cultural values, so as to increase the competitiveness and economic welfare of the Balinese community in Mataram.